Association between reduced fetal movements at term and abnormal uterine artery Doppler indices. (15th April 2014) - Pagani, G.; D'Antonio, F.; Khalil, A.; Akolekar, R.; Papageorghiou, A.; Bhide, A.; Thilaganathan, B.
ABSTRACT Objectives To evaluate the association between second‐trimester uterine artery (UtA) Doppler pulsatility index (PI) with reduced fetal movements (RFM) and adverse pregnancy outcome at term. Methods This was a retrospective cohort study of all singleton pregnancies referred for routine antenatal care at a fetal medicine unit over a 5‐year period. UtA Doppler indices were obtained at the time of the routine anomaly scan between 19 and 23 weeks' gestation to assess the risk for pre‐eclampsia. All episodes of RFM within 1 month of the expected date of delivery were recorded. Regression and sensitivity analyses were used to assess the relationship between UtA‐PI with RFM, small‐for‐gestational‐age (SGA) fetuses and stillbirth after 36 weeks' gestation. Results Overall, 17 649 pregnancies were included in the analysis, of which 742 presented with RFM, 1494 gave birth to an SGA newborn and 53 were complicated by stillbirth after 36 weeks' gestation. Logistic regression analysis showed a significant and independent association between UtA‐PI and RFM (odds ratio (OR), 5.03 (95% CI, 4.21–6.01); P < 0.001), SGA (OR 2.41 (95% CI, 2.09–2.79); P < 0.001) and stillbirth (OR 1.55 (95% CI, 1.21–1.98); P< 0.001). The association between UtA‐PI and SGA was significantly stronger in women presenting with RFM than in the rest of the cohort (P < 0.001). Similarly the association between UtA‐PI and RFM was significantly stronger in those pregnancies complicated by stillbirth (P < 0.001). Conclusions Compared with normal pregnancies, those complicated by RFM, SGA and stillbirth at term had higher UtA‐PI at 19–23 weeks' gestation. These findings support the assertion that RFM at term is independently related to placental dysfunction and subsequent risk for SGA and stillbirth. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd.